Integration-Interconnection Paradigm as An Academic Strategy in The Deradicalization of Religious Thought in Islamic Higher Education - Rahmat, Ali; Bakar, M. Yunus Abu; Mas’ud, Ali; Karomah, Fika Fitrotin (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
The purpose of this article is to explicitly present Amin Abdullah’s intellectual contribution in integrating religious sciences and general sciences into an inseparable unity through the Integration–Interconnection Paradigm, thereby eliminating the dichotomy of knowledge. This study employs a library research approach, collecting data from primary sources, including M. Amin Abdullah’s ideas on the Integration–Interconnection Paradigm, developed at UIN Sunan Kalijaga Yogyakarta, as well as secondary sources that support the study’s main themes. The data analysis technique used is descriptive analysis, in which the collected data are processed and systematically reported. The findings indicate that the Integration–Interconnection Paradigm, developed by Amin Abdullah, is grounded in the concept of Revelation Guiding Knowledge, which positions revelation as the primary guide for the development of science and knowledge. This paradigm is based on three complementary epistemological frameworks that together form an integrated whole: bayānī, burhānī, and ‘irfānī. In the context of Islamic higher education, the Integration–Interconnection Paradigm is implemented across four levels: philosophical, material, methodological, and strategic. Furthermore, this paradigm plays a significant role in efforts to prevent and counter religious radicalism and extremism. Thus, this article contributes to the academic literature by strengthening religious moderation across several Islamic higher education institutions.